The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jipb.12504
|View full text |Cite
|
Sign up to set email alerts
|

SUMO E3 Ligases GmSIZ1a and GmSIZ1b regulate vegetative growth in soybean

Abstract: SIZ1 is a small ubiquitin‐related modifier (SUMO) E3 ligase that mediates post‐translational SUMO modification of target proteins and thereby regulates developmental processes and hormonal and environmental stress responses in Arabidopsis. However, the role of SUMO E3 ligases in crop plants is largely unknown. Here, we identified and characterized two Glycine max (soybean) SUMO E3 ligases, GmSIZ1a and GmSIZ1b. Expression of GmSIZ1a and GmSIZ1b was induced in response to salicylic acid (SA), heat, and dehydrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 51 publications
(87 reference statements)
2
20
0
Order By: Relevance
“…Small ubiquitin‐related modifier conjugation was lower in siz1 mutants than in wild‐type Arabidopsis plants, even under heat stress . Conversely, heat‐induced sumoylation of target proteins was observed in several previous studies . In addition, rice E3 SUMO ligases OsSIZ1 and OsSIZ2 were involved in sumoylation of target proteins under heat stress , and transgenic Arabidopsis overexpressing tomato E3 SUMO ligase SISIZ1 also accumulated SUMO conjugates in response to heat stress .…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Small ubiquitin‐related modifier conjugation was lower in siz1 mutants than in wild‐type Arabidopsis plants, even under heat stress . Conversely, heat‐induced sumoylation of target proteins was observed in several previous studies . In addition, rice E3 SUMO ligases OsSIZ1 and OsSIZ2 were involved in sumoylation of target proteins under heat stress , and transgenic Arabidopsis overexpressing tomato E3 SUMO ligase SISIZ1 also accumulated SUMO conjugates in response to heat stress .…”
Section: Discussionmentioning
confidence: 61%
“…Numerous proteins are conjugated to SUMO in response to heat stress, suggesting that sumoylation contributes to heat tolerance . Here, AtSIZ1 was polyubiquitinated rather than sumoylated under heat stress conditions (Fig.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Studies in A. thaliana have shown that the SUMOylation pathway is mainly mediated by the SUMO E3 ligase SIZ1. Currently, SIZ1 genes have been isolated from plants such as rice (PARK et al 2010), Dendrobium nobile (Liu et al 2015), apple (Zhang et al 2016), soybean (Cai et al 2017) and tomato (Zhang et al 2017), but no study on cloning the gene SIZ1 and its interaction with ICE1 in forest trees. The coding sequence of EcaSIZ1 , which was isolated in this study, is similar to the cloned SIZ1 protein in the above plants, and also has similar protein secondary domains such as MIZ1/SP zinc finger domain, SAP domain, PINIT domain, SXS domain and PHD domain.…”
Section: Discussionmentioning
confidence: 99%